MYSTICAL PATH TO PEACE: An Ethnographic Study of the Maizbhandari Sufi Culture in Chittagong, Bangladesh - Tanjim, Azmain; Hossain, Md. Didar (Asia-Pacific Journal on Religion and Society, 2023)
This study explores the Maizbhandari Sufi culture, a unique indigenous Sufi tradition that originated in Chittagong, Bangladesh. Employing an ethnographic approach, the research was conducted in Maizbhandar (Fatikchhari, Chittagong), the spiritual center of the tariqa. Data were gathered through 30 in-depth interviews, three focus group discussions involving 18 participants, and one key informant interview, all selected via purposive sampling. Thematic analysis was used to examine the qualitative data. Findings reveal the distinctive belief systems, rituals, spiritual practices, major festivals, and gender dynamics within the Maizbhandari tradition. The study concludes that Maizbhandari Sufism promotes values of love, peace, patience, and humanity, offering an inclusive and harmonious spiritual path that resists religious extremism and fosters social cohesion